Conceptualizing the development of road to success (RoSe) game in enhancing students' academic motivation / Nor Aziah Abd Kadir, Musramaini Mustapha and Hasnizawati Hashim - Abd Kadir, Nor Aziah; Mustapha, Musramaini; Hashim, Hasnizawati (2016)
There are many motivation programs have been organized by the faculty in order to increase student awareness on the importance of academic excellence, such as motivational talk and physical activities. However, these types of motivation programs sound very common to most of the tertiary education's students and they are not able to attract students' participation. Students sometimes attend the programs for the sake of avoiding penalties from the university if they engage in absenteeism. This paper provides a comprehensive study on literatures that discuss on the contribution of the interactive motivational game to students' academic performance. Based on the Constructivist Theory, the element of active participation in fun based game should be introduced to attract students' interest. Thus, the Road to Success (RoSe) is developed to improvise the existing programs which are too common and dull. RoSe is an interactive motivational game that creates fun in activities. To play the game, students need to roll the dice and move up the cips in a race against their opponents. When they reach at certain pit stops, they need to do the activities based on the instruction given. The activities may improve students' memorization skills, knowledge on vocabulary and mind's creativity. Students will enjoy hours of endless fun with this engaging game and promote teamwork relationship. RoSe also emphasizes on few emoticons represent the real environment in students' life at university. The game is easy to conduct and may be applied in any motivational programs as it can attract students' participation and motivation to succeed.